Toward an Islamic Values Framework for Mathematics Education: Evidence from Classroom Practices - Ari Limay Trisno Putra; Ibnu Imam Al Ayyubi; Reziq Ridho; Muhammad Farhan Habibi (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2026)
Amid the rapid development of information technology, Islamic da'wah faces significant challenges in reaching younger generations who are increasingly exposed to diverse streams of digital information. One potential approach to addressing this challenge is to utilize mathematics education as a medium for da'wah, connecting scientific concepts with religious teachings. This study employs a qualitative approach using a case study method to explore the strategies and challenges of Islamic da'wah in integrating the values of mathematics education in the digital era. Data were collected through in-depth interviews with da'wah leaders, educators, mathematics education practitioners, and audiences involved in mathematics-based da'wah activities. In addition, document analysis was conducted on da'wah content disseminated through digital platforms such as social media, websites, and mobile applications. Data collection techniques included in-depth interviews and observations. The data were analyzed using thematic analysis. This article examines strategic approaches to integrating Islamic religious values into mathematics learning while identifying the pedagogical and technological challenges that accompany this process. Academically, this study contributes to the formulation of a conceptual framework for mathematics-based da'wah in the digital era, grounded in empirical findings from da'wah leaders and mathematics educators. By bridging the discourse between Islamic education and science education, this study proposes an integrated value-based mathematics learning model that is both theoretical and practical within the context of contemporary digital education.